Reflections - Yu, Ming Dong (2014)
The project “reflections” is a project that creates an image of reflection with 2 images merging together. The project merges 2 images together, placing one on top the other. By doing so, the output image shall have a new aesthetic appeal and shall be further discuss in this paper.